Synovial Osteo-chondromatosis: in Regards with a Case - Dianarelys Villafuerte Delgado; Mercy Guadalupe Heras Heras; Félix González Pérez (Revista Finlay)
Synovial chondromatosis is a benign, infrequent lesion with a generally synovial membrane mono-articular location. It affects one in every 100,000 inhabitants. It is 2 times more frequent in men, and mainly affects large joints: knee (70 %), hip (20 %) and shoulder (19 %). Imaging studies are essential for diagnosis. A case of 20 year old patient is presented who after performing systematic physical exercises began with left shoulder volume increased and limited movement; he consulted the orthopedic and was prescribed treatment after physical examination and imaging studies. The case is presented because it is an infrequent medical entity in which imaging studies have a vital role for the diagnosis and posterior treatment.